MP-6 Coccidiosis Intestinal Dysmotility in C57BL/6 Mice - Riki Siswadi; Ayako Yoshida; Hiroyuki Satoh; Nariaki Nonaka (Hemera Zoa, 2018)
Recently, anecdotal report was arisen that coccidiosis in cattle resulted in delayed intestinal motility. The occurrence of delayed intestinal motility has been never briefly reported. However, some study indicated a delay in intestinal motility. A study in cattle coccidiosis reported a transient increase of nutrients apparent digestibility, especially of crude fiber index, during clinical coccidiosis and that anorexia and intestinal leakage impaired the nitrogen balance, causing weight depression. The observation may have reflected intestinal hypomotility, however, this work did not observe the intestinal motility directly. Another study indicated that Eimeria infection in rabbit could induce intestinal motility disturbance. The disturbance, however, did not indicate as general delay in intestinal transit, because some part of the intestine experienced faster motility and another part indicated slower motility.As one of the cosmopolitan diseases of production animal, the occurrence of intestinal dysmotility by coccidiosis need to be clarified. And a control measure against intestinal dysmotility of coccidiosis need to be proposed soon after the clarification of its clinical existence. Therefore, we designed a study with murine Eimeria as model to provide evidence for better approach toward this emerging issue.